Area under curve of temporal estradiol measurements for prediction of the detrimental effect of estrogen exposure on implantation. Issue 2 (November 2016) - Kutlu, Tayfun; Ozkaya, Enis; Ayvaci, Habibe; Devranoglu, Belgin; Sanverdi, Ilhan; Sahin, Yavuz; Senol, Taylan; Karateke, Ates
Abstract: Objective: To assess whether the area under the curve of temporal estradiol measurements (AUCEM) during cycles of assisted reproductive technology (ART) can be used to predict failure of implantation and clinical pregnancy. Methods: In a prospective study, women aged 24–39 years undergoing ART at a center in Turkey were enrolled between January and December 2014. Eligible patients had a regular menstrual cycle, normal levels of serum prolactin, and no hormone treatment within the past 3 months. The area under the curve of the time course of estradiol measurements was calculated for each participant, and assessed for its ability to predict successful implantation. Results: Among 282 participants, 109 (38.6%) women had successful implantation. There was a significant difference between the two groups of women in AUCEM, estradiol per day (AUCEM divided by duration of stimulation), and endometrial thickness on the day of human chorionic gonadotropin administration ( P < 0.05 for all). Conclusion: The area under the curve of estradiol measurements during ART cycles might be useful for predicting failure of implantation and clinical pregnancy.